1995
DOI: 10.1126/science.7892601
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibition: An Approach to Drug Development

Abstract: Protein tyrosine kinases (PTKs) regulate cell proliferation, cell differentiation, and signaling processes in the cells of the immune system. Uncontrolled signaling from receptor tyrosine kinases and intracellular tyrosine kinases can lead to inflammatory responses and to diseases such as cancer, atherosclerosis, and psoriasis. Thus, inhibitors that block the activity of tyrosine kinases and the signaling pathways they activate may provide a useful basis for drug development. This article summarizes recent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
1,050
1
4

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,566 publications
(1,080 citation statements)
references
References 97 publications
25
1,050
1
4
Order By: Relevance
“…The specific EGFR-blocking tyrphostins, AG 1478 and AG 1517, were kindly provided by Drs Gazit and Levitzki (Jerusalem, Israel), (Fry et al, 1994;Osherov and Levitzki, 1994;Levitzki and Gazit, 1995). They were dissolved in dimethyl sulphoxide (DMSO); for application in cell culture, the final DMSO concentration in the assays was < 0.…”
Section: Materials and Methods Cells And Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific EGFR-blocking tyrphostins, AG 1478 and AG 1517, were kindly provided by Drs Gazit and Levitzki (Jerusalem, Israel), (Fry et al, 1994;Osherov and Levitzki, 1994;Levitzki and Gazit, 1995). They were dissolved in dimethyl sulphoxide (DMSO); for application in cell culture, the final DMSO concentration in the assays was < 0.…”
Section: Materials and Methods Cells And Reagentsmentioning
confidence: 99%
“…Although some of the clinical data obtained so far are encouraging, the general impression emerges from these studies that antibody treatment alone will not be sufficient to combat EGFR-driven tumours, but will need combination with further antiproliferative agents (Baselga and Mendelsohn, 1994b). A further strategy to block EGFR signalling would be the specific inhibition of receptor tyrosine kinase activity (Gibbs and Oliff, 1994;Levitzki and Gazit, 1995). Recent efforts to obtain synthetic EGFR kinase inhibitors yielded quite potent and specific compounds, which might lead to useful pharmacological agents in the future.…”
mentioning
confidence: 99%
“…Transforming growth factor a and erbb-1 are upregulated in malignancies of many different organs, including HCC. Novel therapeutic approaches have been focusing on the possible benefit of blocking TGFa-evoked signal transduction on the cell surface, for example, by erbb-1 blockade (Levitzki and Gazit, 1995;Mendelsohn, 1997). The present study shows that treatment with mature TGFa stimulated DNA synthesis rather in proTGFa-neg than in proTGFa-pos hepatocytes, which was abrogated by an erbb-1-specific tyrosine kinase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The ectodomain of the pro-peptide may be shed from the cell surface, where it may bind to and activate the erbb-1 receptor, that confers the growth signal via phosphorylation cascades to the nucleus (Massagué, 1990;Yarden and Sliwkowski, 2001). Considering the upregulation of TGFa in human malignancies, including liver cancer, hope focuses on the possible therapeutic benefit of blocking TGFaevoked signal transduction on the cell surface, for example, by blockade of the receptor or of ligand -receptor interactions (Levitzki and Gazit, 1995;Mendelsohn, 1997). In a recent study, however, we have shown that hepatocytes in the intact liver and in primary culture synthesise proTGFa that translocates to the nucleus, where it appears to be involved in the mitogenic response of the cell (Grasl-Kraupp et al, 2002).…”
mentioning
confidence: 99%
“…In an earlier study on the action of TK inhibitors on L-type Ca 2 þ current (I Ca,L ) in guinea-pig ventricular myocytes (Ogura et al, 1999), we observed that both genistein and the structurally and mechanistically different A23 (Levitzki & Gazit, 1995) caused development of outward current at 0 mV. The current appeared to be CFTR Cl À current (I Cl(CFTR) ), and was not further investigated.…”
Section: Introductionmentioning
confidence: 96%